Synopsis of Cnidoscolus (Euphorbiaceae) in midwestern Brazil, including taxonomic updates, a new species, and a reestablishment of C. neglectus - de Oliveira, Cellini Castro; de Melo, André Laurênio; Da Silva, Marcos José (Phytotaxa, 2021)
A synopsis of the genus Cnidoscolus is presented for the midwestern region of Brazil, which resulted from the analysis of about 1,200 specimens from 62 national and foreign herbaria, including type collections. Observations of populations in field were also made. Nine species are recognized, one of which, C. mcvaughii, is new to science. It is described and illustrated, and comments about its geographic distribution, morphological relationships, systematic position, phenology, and conservation status are provided, as well as images and a map. The other species are contrasted by a dichotomous key. Also, distributional information, maps, conservation evaluations, images and morphologically diagnoses are included. Eight synonymizations, one lectotypification, a neotypifcation, and the re-establishment of C. neglectus are proposed.